(untitled) (Scientific journal of the Fergana State University, 2024)
This article, dedicated to the reforms being implemented by President Sh.M. Mirziyoyev in the field of education and upbringing, focuses on the role of the cooperation concept. The article analyzes the role that preschools, schools, higher and secondary special education systems, and scientific and cultural institutions, as four integral links of the education system defined by the President, should play in the new era of renaissance. It also emphasizes the importance of fulfilling the tasks outlined in the cooperation concept among families, mahallas, and educational institutions in raising the young generation. The main goal of the concept is to help each child find their place in life and become a humane individual. The article highlights the measures taken to ensure cooperation among families, mahallas, and educational institutions, including the work carried out based on Decree No. 175 adopted in 2012. The concluding part stresses the invaluable role of families and educational institutions in nurturing well-rounded and spiritually mature individuals. This article serves as a research material aimed at understanding the role and significance of the cooperation concept in improving the quality of education and upbringing.